PENERAPAN MEDIA PEMBELAJARAN AUDIO VISUAL UNTUK MENINGKATKAN HASIL BELAJAR PENDIDIKAN PANCASILA SISWA KELAS V SD NEGERI 17 LUBUK LINGGAU - Fuan Maharani; Ani Fiani; Dedy Firduansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the Application of Audio Visual Media in Pancasila Education Learning for Fifth Grade Students of SD Negeri 17 Lubuk Linggau. This research method is pre-experimental, with the design used is one-group pretest-posttest design. The population in this study were all fifth grade students of SD Negeri 17 Lubuklinggau. Sampling was done using saturated sampling technique, namely in fifth grade of SD Negeri 17 Lubuklinggau totaling 28 students as a sample class. Data collection techniques using multiple choice tests both before and after the implementation of the instructional media. Data analysis techniques with steps: normality test and z test. Based on the results of the Z-test analysis with a confidence level obtained α = 0.05 data z count = 6.52 and Z table = 1.64 then the data shows that the Zcount value > Ztable. The average value of student pretest is 41.46 and the average value of posttest is 83.25, so it can be said that H0 is rejected and Ha is accepted. Thus, it can be concluded that the application of Audio Visual Media in Pancasila education learning for fifth grade students of SD Negeri 17 Lubuk Linggau was significantly completed.